2023
DOI: 10.1101/2023.02.24.529990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV-1 Gag colocalizes with euchromatin histone marks at the nuclear periphery

Abstract: The retroviral Gag protein of human immunodeficiency virus type 1 (HIV-1) plays a central role in the selection of unspliced viral genomic RNA for packaging into new virions. Previously, we demonstrated that full-length HIV-1 Gag undergoes nuclear trafficking where it associates with unspliced viral RNA (vRNA) at transcription sites. To further explore the kinetics of HIV-1 Gag nuclear localization, we used biochemical and imaging techniques to examine the timing of HIV-1 entry into the nucleus. We also aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 82 publications
(137 reference statements)
2
7
0
Order By: Relevance
“…When the HIV-1 Gag interactomes identified by other laboratories were compared to the interacting proteins identified by us in this report, 190 common proteins were found by at least two independent laboratory groups. Further experimentation will be needed to validate each of these factors to determine whether they play important roles in retrovirus replication or pathogenesis (Fig5).Our past and present cell fractionation experiments demonstrated that, in addition to being present in the nucleoplasm, both the RSV and HIV-1 Gag proteins can be extracted from euchromatin and heterochromatin fractions, complementing our recently published report indicating that HIV-1 Gag localizes with euchromatin marks at the nuclear periphery(9,10). These results suggest that HIV-1 Gag may be specifically targeted to a chromatin-associated compartment through interactions with host nuclear binding partners.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…When the HIV-1 Gag interactomes identified by other laboratories were compared to the interacting proteins identified by us in this report, 190 common proteins were found by at least two independent laboratory groups. Further experimentation will be needed to validate each of these factors to determine whether they play important roles in retrovirus replication or pathogenesis (Fig5).Our past and present cell fractionation experiments demonstrated that, in addition to being present in the nucleoplasm, both the RSV and HIV-1 Gag proteins can be extracted from euchromatin and heterochromatin fractions, complementing our recently published report indicating that HIV-1 Gag localizes with euchromatin marks at the nuclear periphery(9,10). These results suggest that HIV-1 Gag may be specifically targeted to a chromatin-associated compartment through interactions with host nuclear binding partners.…”
supporting
confidence: 83%
“…Tables 3 and 4 list the proteins involved in transcription and splicing, respectively, for the RSV pulldowns. Similarly, Tuffy et al and Chang et al (9, 10) both demonstrated that HIV-1 Gag localizes to transcriptionally active regions in HeLa cells and T cells reactivated from latency. Given these findings, it is feasible that HIV-1 Gag interacts with host nuclear factors involved in transcription, RNA processing, and chromatin remodeling.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…HIV-1 Gag forms focal RNP complexes with nascent USvRNA in the nucleus, and traffics to the major viral RNA transcription site in T cells reactivated from latency [ 9 ]. Nuclear localization of HIV-1 Gag occurs in a concentration-independent manner shortly after Gag synthesis begins, and Gag colocalizes with transcriptionally-active euchromatin near the nuclear periphery [ 10 ]. The function(s) of these nuclear RNPs has yet to be thoroughly investigated, although these data demonstrate that both RSV and HIV-1 Gag proteins traffic to transcription sites and associate with their cognate USvRNAs.…”
Section: Introductionmentioning
confidence: 99%